N2 and P3 responses in adolescents with non-suicidal self-injury and their association with clinical outcomes: a cohort follow-up study based on the affective stroop paradigm - Yin, Fei; Si, Feng; Jiang, Wenlong; Huo, Shuhui; Wang, Binquan; Yang, Nan; Cao, Jianqin (Frontiers in Psychiatry, 2025)
BackgroundNon-suicidal self-injury (NSSI), a prevalent psychiatric behavioral problem in adolescents, manifests diverse outcomes including cessation of remission, aggravation, and even progression to suicidal behaviors. It is crucial to track its progression and identify predictors of clinical outcomes in NSSI. The aim of this study was to determine whether the N2 and P3 responses in adolescents with NSSI were defective in the presence of the affective Stroop paradigm and associated with their clinical outcomes.MethodsParticipants were selected from an ongoing longitudinal study designed to predict clinical outcomes of NSSI in adolescents. Twenty-six in the remission group (RG), twenty-nine in the aggravation group (AG), and twenty-seven in the healthy group (HG) completed the affective Stroop task with EEG. Accuracy and reaction times (RTs) served as behavioral indexes, while N2 and P3 amplitude served as electrophysiological indexes; they were analyzed across groups. We used the EEGNet model to predict the NSSI clinical outcomes with EEG component.ResultNo significant main effects of group or affective stimuli or an effect of their interaction were observed on accuracy (p > 0.05). For RTs, there was a significant main effect of group, with slower RTs observed in the AG compared to the HG (p < 0.05). For N2 and P3 amplitude, there were significant main effect of group and affective stimuli and an effect of their interaction. Under neutral stimuli, the N2 amplitude in the AG was significantly larger than that in the RG (p < 0.05) and the HG (p < 0.01), while the P3 amplitude in AG was significantly smaller than that in the HG (p < 0.05), but there was no significant difference between RG and AG(p > 0.05). The EEGnet model demonstrated that N2 amplitudes elicited by neutral stimuli achieved the highest classification accuracy (92.31%) for predicting clinical outcomes of NSSI.ConclusionThe findings indicate that NSSI is linked to cognitive processing deficits, including impaired control and resource allocation to stimuli. Additionally, N2 amplitudes were shown to reliably predict clinical outcomes in NSSI.